Bariatric surgery in the treatment of morbid obesity : long term outcomes and comparison of laparoscopic sleeve gastrectomy with Roux-en-Y gastric bypass - Helmiö, Mika (fi=Turun yliopisto|en=University of Turku|, 2020)
Obesity is currently one of the greatest global health problems. It is associated with increased morbidity and mortality, worsened quality of life (QOL) and significant health care costs. For morbidly obese patients, bariatric surgery is the only effective treatment option showing good and sustainable long-term weight loss and remission or improvement of obesity related comorbidities. Laparoscopic Roux-en-Y gastric bypass (LRYGB) is the gold standard of bariatric surgery with demonstrated longterm efficacy. During the last years, laparoscopic sleeve gastrectomy (LSG) has become the most common bariatric procedure despite the lack of long-term followup results at that time. The main aim of this thesis was to compare the short and long-term outcomes on weight loss, obesity related co-morbidities, and QOL after LSG and LRYGB in the treatment of morbid obesity in a randomized clinical multicenter equivalence trial (SLEEVEPASS). In addition, this thesis aimed to assess the QOL improvement after laparoscopic gastric banding (LGB) and to compare it with the QOL of the general population. The operative time of LSG was shorter with no difference in early (30 days) overall morbidity between LSG and LRYGB. At 5-year follow-up, the primary endpoint of percent excess weight loss (%EWL) was 57% after LRYGB and 49% after LSG. The mean difference was not statistically significant based on the prespecified equivalence margins. At 5 years, there were no differences regarding the long-term resolution of type 2 diabetes or dyslipidemia, improvement of QOL, morbidity, and mortality, but hypertension resolution was superior after LRYGB. QOL improved significantly after LAGB and was maintained at five-year follow-up but did not reach the level of the general population.

Bariatrinen kirurgia sairaalloisen lihavuuden hoidossa: pitkäaikaistulokset ja vertailu mahalaukun kavennusleikkauksen ja ohitusleikkauksen välillä Lihavuus on yksi suurimpia maailmanlaajuisia terveysongelmia. Siihen liittyy lisääntynyt sairastavuus ja kuolleisuus, huonontunut elämänlaatu sekä merkittäviä terveydenhuollon kustannuksia. Lihavuuskirurgia on ainoa hoitomuoto, jolla saavutetaan hyvät pitkäaikaistulokset painonlaskun sekä sairaalloiseen lihavuuteen liittyvien liitännäissairauksien paranemisen osalta. Mahalaukun ohitusleikkaus (bypass) on vakiintunut leikkausmenetelmä, jonka teho on osoitettu pitkäaikaisseurannassa. Viime vuosina mahalaukun kavennusleikkauksesta (sleeve) on tullut yleisin lihavuuskirurginen leikkausmenetelmä ilman käytettävissä olevia pitkäaikaistuloksia. Tämän väitöskirjatyön tarkoituksena oli vertailla mahalaukun kavennus- ja ohitusleikkauksen tuloksia painonlaskun, liitännäissairauksien paranemisen sekä elämänlaadun osalta satunnaistetussa kliinisessä monikeskus-ekvivalenssitutkimuksessa (SLEEVEPASS). Lisäksi tutkittiin mahapantaleikkauksen jälkeistä elämänlaadun paranemista ja vertailtiin sitä väestön yleiseen elämänlaatuun. Varhaisvaiheen tuloksissa kavennusleikkauksen leikkausaika oli lyhyempi, mutta komplikaatioiden määrässä ei ollut eroa ohitusleikkaukseen verrattuna. Tutkimuksen ensisijainen päätetapahtuma eli ylipaino-osuuden prosentuaalinen lasku (%EWL) viiden vuoden seurannassa oli ohitusleikkauksen jälkeen 57% ja kavennusleikkauksen jälkeen 49%. Keskimääräinen ero ei ollut tilastollisesti merkitsevä perustuen ennalta määriteltyihin ekvivalenssirajoihin. Leikkausmenetelmien välillä ei ollut eroa tyypin 2 diabeteksen, hyperkolesterolemian ja elämänlaadun paranemisessa, eikä sairastavuudessa ja kuolleisuudessa, mutta verenpainetauti parani useammin ohitusleikkauksen jälkeen. Mahapantaleikkauksen jälkeen elämänlaatu parani merkitsevästi viiden vuoden seuranta-aikana, mutta lihavuuskirurgisten potilaiden elämänlaatu oli vertailuväestöä huonompi.